Health Services Use by Children in the Welfare System Who Died by Suicide - Ruch, Donna A. (Pediatrics, 2021)
OBJECTIVES: To examine characteristics and health service use patterns of suicide decedents with a history of child welfare system involvement to inform prevention strategies and reduce suicide in this vulnerable population. METHODS: A retrospective matched case-control design (120 suicide decedents and 1200 matched controls) was implemented. Suicide decedents included youth aged 5 to 21 who died by suicide and had an open case in Ohio’s Statewide Automated Child Welfare Information System between 2010 and 2017. Controls were matched to suicide decedents on sex, race, and ethnicity. Comparisons were analyzed by using conditional logistic regressions to control for matching between the suicide and control groups. RESULTS: Youth in the child welfare system who died by suicide were significantly more likely to experience out-of-home placements and be diagnosed with mental and physical health conditions compared with controls. Suicide decedents were twice as likely to access mental health services in the 1 and 6 months before death, regardless of the health care setting. A significantly higher percentage of suicide decedents used physical health services 6 months before their death or index date. Emergency department visits for both physical and mental health conditions were significantly more likely to occur among suicide decedents. CONCLUSIONS: Suicide decedents involved in the child welfare system were more likely to use both mental and physical health care services in the months before their death or index date. Findings suggest that youth involved in the child welfare system may benefit from suicide prevention strategies in health care settings.